2020
DOI: 10.3390/su12166661
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Media in Health Safety Evaluation of a Tourism Destination throughout the Travel Planning Process

Abstract: This research aims at identifying the role of social media in evaluating the attractiveness of a tourism destination, with special emphasis on the health safety of the destination. Consistent with this objective, a survey has been carried out on a sample of 675 Romanian social media users. The research results led to the development of a model based on structural equation modeling. The model includes nine latent variables that were structured taking into account different behavioral aspects related to the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 78 publications
0
22
0
Order By: Relevance
“…Conversely, people may become more skeptical and reluctant to adopt recommended health behaviors if they mistrust the media (Klemm, Das, and Hartmann 2016). Tourism research revealed that tourists mainly apply media information to evaluate health safety and select tourism destinations (e.g., Țuclea, Vrânceanu, and Năstase 2020). In a postpandemic recovery, the media is an important marketing strategy for destinations to increase tourism demand (Bhati et al 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conversely, people may become more skeptical and reluctant to adopt recommended health behaviors if they mistrust the media (Klemm, Das, and Hartmann 2016). Tourism research revealed that tourists mainly apply media information to evaluate health safety and select tourism destinations (e.g., Țuclea, Vrânceanu, and Năstase 2020). In a postpandemic recovery, the media is an important marketing strategy for destinations to increase tourism demand (Bhati et al 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our study forges new paths by exploring perceived health safety as a key factor, given the current unstable scenario. The marketing literature recognizes health safety as a destination-based tourist perception, which gains relevance during the travel planning process ( Ț;uclea et al, 2020 ). In the context of the COVID-19 pandemic, health safety perceptions have become increasingly relevant for determining tourism outcomes ( Dube et al, 2021 ).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…It is critical that information on each tourist destination be available in every travel agency and on every website so that travelers may learn more about the destination before they arrive and avoid wasting time, money, and effort. They utilize this information to choose the greatest tourist attractions or activities that would interest them, as well as whether or not traveling is secure and safe (Tuclea et al, 2020). As Lee et al (2019) stated, travelers use both online and offline information sources to obtain data on their desired location, which may influence their decision to visit.…”
Section: International Journal Of Research Studies In Management 111mentioning
confidence: 99%